Three-level Cascaded Inverter Based D-STATCOM Using Decoupled Indirect Current Control - Coteli, Resul; Deniz, Erkan; Tuncer, Servet; Dandil, Besir (Taylor & Francis Ltd, 2011)
In this paper, experimental setup of three-level cascaded inverter based 380V/+/- 25kVAR D-STATCOM using decoupled indirect current control method (DICC) is realized. AC and DC side of D-STATCOM is modelled in dq-axis on account of D-STATCOM's controlling. DICC is used for control of D-STATCOM's dq-axis currents independently. Gate pulses for inverter are generated with multilevel sinusoidal pulse width modulation (SPWM) technique. In this study, controller card used for signal processing is dSPACEs DS1103. The control algorithm is prepared by the help of MATLAB/Simulink (R) software. This algorithm is converted to C language by using Matlab/Real-Time Workshop and downloaded to DS1103's program memory by dSPACE/Real-Time Interface. Implemented experimental setup is tested by changing reference reactive current (i(qref)) +20A to -20A and obtained results from this test are given.
Keywords: Cascaded inverter; D-STATCOM; DS1103; Decoupled Indirect Current Control